Human, Technologies and Quality of Education, 2022 2022
DOI: 10.22364/htqe.2022.16
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Digital Competence: A Focus Group Study From the Perspective of the Medical College Students

Abstract: Over the last decade, learning and working in medicine has been increasingly influenced by digital tools. Today’s medical students are growing up in a digital age where digital tools and devices are a regular part of professional life. The development of digital competence is crucial for healthcare education, as healthcare professionals will be the ones helping orientate patients in digital healthcare systems and tools. This study aims to explore the opinions and experiences of medical college students regardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The labour market increasingly expects competences like the ability to resolve nonstandard problem situations by using existing digitalisation possibilities and to develop new innovative solutions. Digital competence is related to the application of information and communication technology solutions for supporting tasks in the workplace, and like other transversal competences, it can be transferred among fields [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The labour market increasingly expects competences like the ability to resolve nonstandard problem situations by using existing digitalisation possibilities and to develop new innovative solutions. Digital competence is related to the application of information and communication technology solutions for supporting tasks in the workplace, and like other transversal competences, it can be transferred among fields [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in studies regarding the development of the digital competence, it has been found that there is an interaction of various factors in its development at the individual, microsystem, exosystem and macrosystem levels-personal factors (self-confidence in using ICTs, attitudes towards ICTs, prior training on ICTs, motivation), learning design (online, blended learning), lecturers' digital competence and external aspects (family support, COVID-19 pandemic) [13]. In studies regarding entrepreneurial ability, the interaction and synergy of various factors are underlined (e.g., innate entrepreneurial aptitude, sociological conditions, and educational programmes), and the lack of any component limits the individual potential of an entrepreneur [22].…”
Section: Introductionmentioning
confidence: 99%